Subacute Cutaneous Lupus Erythematosus-Like Eruption Induced by EGFR -Tyrosine Kinase Inhibitor in EGFR-Mutated Non-small Cell Lung Cancer: A Case Report - Ferro, Alessandra; Filoni, Angela; Pavan, Alberto; Pasello, Giulia; Guarneri, Valentina; Conte, PierFranco; Alaibac, Mauro; Bonanno, Laura (Frontiers in Medicine, 2021)
EGFR tyrosine kinase inhibitors (TKIs) are the front-line treatment in EGFR mutation positive advanced non-small cell lung cancer (aNSCLC) patients. Generally, they are well tolerated but skin toxicity is common (45–100% of patients) and may adversely affect quality of life. Pathogenesis of cutaneous side effects is usually linked to EGFR expression in normal cells of the epidermis and not immune-related. Subacute cutaneous lupus erythematosus (SCLE) is an autoimmune disease and about 40% of SCLE cases are drug related, but no reports are available involving osimertinib. Our report depicts a drug induced-SCLE (DI-SCLE) caused by erlotinib and worsened by osimertinib. The adverse event is characterized by the absence of systemic symptoms. Diagnosis has been performed by skin biopsy and the conditions improved with systemic steroids administration and EGFR-TKIs discontinuation. The report underlines the importance of a complete dermatologic diagnosis of skin lesions induced by EGFR inhibitors, according to symptom severity and timing of improving with standard clinical management. The diagnosis of immune-related skin toxicity in this context affects the treatment and the outcome of skin toxicity and must be taken into account when planning subsequent treatments, potentially including immune checkpoint inhibitors (ICIs).